2023
DOI: 10.3390/ani13091511
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Co-Infection by Streptococcus suis and Haemophilus parasuis Reveals Influences on Biofilm Formation and Host Response

Abstract: Streptococcus suis (S. suis) and Haemophilus parasuis (H. parasuis) are two primary pathogens currently affecting the porcine industry. They often cause encephalitis and arthritis. They also frequently co-infect in clinical settings. In the current study, we identified significant correlations between S. suis and H. parasuis. The results from CI versus RIR suggested that S. suis and H. parasuis were competitive in general. Compared to mono-species biofilm, the biomass, bio-volume, and thickness of mixed-specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Currently, due to the continuous development of pig farm intensification, there is a prevalence of GPS-caused diseases in many regions of China, posing a serious threat to the pig farming industry. In recent years, there has been an increase in morbidity and mortality caused by mixed or secondary infections of SS and GPS [1,5]. In a study conducted by Rao et al in Guangxi Province, China, it was reported that SS accounted for 65.21% of pig respiratory pathogens, GPS accounted for 48.19% of pig respiratory pathogens, whereas mixed infections of both were found to account for 13.10% of all cases [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, due to the continuous development of pig farm intensification, there is a prevalence of GPS-caused diseases in many regions of China, posing a serious threat to the pig farming industry. In recent years, there has been an increase in morbidity and mortality caused by mixed or secondary infections of SS and GPS [1,5]. In a study conducted by Rao et al in Guangxi Province, China, it was reported that SS accounted for 65.21% of pig respiratory pathogens, GPS accounted for 48.19% of pig respiratory pathogens, whereas mixed infections of both were found to account for 13.10% of all cases [34].…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus suis (S. suis, SS) and Glaesserella parasuis (G. parasuis, GPS) are most common pathogens in the world of infected pigs widely; both could cause inflammatory infections such as septicemia, meningitis, polyserositis, arthritis, and pneumonia [1]. The number of incidences of porcine streptococcal disease and GPS disease ranked top 10 swine diseases consistently in China from 2018 to 2021 [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are known to form biofilms in the respiratory mucosa of animals, leading to bronchitis, pneumonia, and lung abscesses. Respiratory biofilm-related infections are of significant concern in livestock farming and captive animal facilities [ 3 , 22 , 23 ].…”
Section: Current Understanding Of Biofilm Formation In Animal Diseasesmentioning
confidence: 99%
“…Systemic invasion is characterized by fibrinous polyserositis inflammation, polyarthritis, and fibrinous meningitis, and causes significant losses to producers due to reduction in weight gain, increases in the use of drugs, dead animals, and carcass depreciation [ 112 ]. Although the role of biofilm in H. parasuis pathogenesis is not clear, the expression of genes with putative function in biofilm formation has been detected, which plays a crucial role in the pathogenesis of the disease [ 22 ].…”
Section: Current Understanding Of Biofilm Formation In Animal Diseasesmentioning
confidence: 99%